PEMETAAN PENGHASIL CENGKEH DENGAN CLUSTER PADA ALGORITMA K-MEANS - Lubis, Zulkarnain; Indrayani, Lilis (Fakultas Teknik, Universitas Tadulako, 2021)
Clove production in Tolitoli Regency, which is spread across all sub-districts, is a producer of cloves. The role of the Plantation Office in categorizing and mapping which sub-districts produces clove production is in the highest or last category. This study conducted grouping of clove-producing areas using the K-means algorithm clustering method, the K-means algorithm has a sensitive problem in determining the partition number of clusters (k), to determine whether the determined cluster is optimal, clustering evaluation is carried out with the Devies Bouldin Index (DBI). This study resulted in three groups producing the most, medium, and few cloves, the results of the evaluation with 3 clusters were optimal for the Devies Bouldin Index (DBI) of 0.390. It was found that the Districts of Damsel, Dampal Utara, Dondo, Basidondo, Lampasio, Dakopamean, and North Tolitoli were included in Cluster 1 (one), Baolan District, Galang into Cluster 2 (two), and Ogoideide in Cluster 3 (three).